Neonatal pulmonary artery thrombosis - Mangesh Jadhav; Ashish Sapre; Swati Garekar; Snehal Kulkarni (Wolters Kluwer Medknow Publications, 2012)
Pulmonary artery thrombosis in neonates is a rare entity. We describe two neonates with this diagnosis; their presentation, evaluation, and management. These cases highlight the importance of this differential diagnosis when evaluating the cyanotic neonate.